Linear and nonlinear optical properties of Gd3+ doped zinc borotellurite glasses for all optical switching applications - Eevon, C.; Halimah, M. K.; Zakaria, A.; Azurahanim, C. A. C.; Azlan, M. N.; Faznny, M. F. (Elsevier, 2016)
In this work, linear and nonlinear optical parameters of zinc borotellurite glasses doped with Gd3+ have been studied for all-optical switching applications. A series of gadolinium zinc borotellurite glasses were synthesized by using conventional melt quenching technique. Optical absorption spectra were recorded by UV–vis spectroscopy. From the optical absorption spectra, the cut-off wavelength, optical band gap, Urbach energy and refractive index have been determined and are related to the structural changes in the glass systems. The nonlinear optical properties of Gd3+ doped glasses are investigated by using Z-scan technique. The values of nonlinear refractive index and absorption coefficient with closed and opened apertures of the Z-scan, respectively, were determined for proper utilization in nonlinear optical devices.